استخدام مواقع التواصل الاجتماعي في تحسين صورة المؤسسة دراسة تحليلية لصفحة فيس بوك المؤسسة الاستشفائية المتخصصة -أحمد بن عبيد-ببرج بوعريريج - ساعد سعود ايمان; اشراف: يوسفي عبد العالي (جامعة المسيلة كلية العلوم الانسانية والاجتماعية, 2026)
تناولت هذه الدراسة موضوع استخدام مواقع التواصل الاجتماعي وبالأخص موقع الفيسبوك في تحسين صورة المؤسسة الاستشفائية المتخصصة أحمد بن عبيد ببرج بوعريريج ولذلك تم اختيار الصفحة الرسمية للمؤسسة كنموذج للدراسة انطلاقا من طرح الإشكالية التالية: كيف يتم استخدام موقع الفيس بوك في تحسين صورة المؤسسة الاستشفائية المتخصصة احمد بن عبيد ببرج بوعريريج لدى جمهورها؟ تسعى هذه الدراسة إلى التعرف على الأهداف التالية: معرفة طبيعة المحتوى المنشور عبر الصفحة الرسمية للمؤسسة الاستشفائية المتخصصة أحمد بن عبيد ببرج بوعريريج ،معرفة طبيعة لغة المحتويات المنشورة عبر الصفحة الرسمية للمؤسسة محل الدراسة على الفيس بوك ،التعرف على أشكال النشر التي تستخدمها المؤسسة محل الدراسة عبر صفحتها الرسمية على الفيس بوك ، رصد مستوى تفاعل الجمهور مع المحتوى الذي تنشره المؤسسة محل الدراسة عبر صفحتها الرسمية على موقع الفيس بوك (من حيث عدد التعليقات، الإعجاب ،المشاركة) التعرف على أهداف الصفحة الرسمية للمؤسسة محل الدراسة، معرفة الجمهور المستهدف من قبل الصفحة الرسمية للمؤسسة محل الدراسة ، معرفة اتجاه الجمهور نحو الصفحة الرسمية للمؤسسة محل الدراسة، التعرف على الفاعلين في الصفحة الرسمية للمؤسسة محل الدراسة ولتحقيق أهداف الدراسة تم الاعتماد على المنهج الوصفي التحليلي من خلال التعريف بمتغيرات الدراسة في الجانب النظري أما في الجانب التطبيقي تم تحليل منشورات الصفحة الرسمية للمؤسسة محل الدراسة باختيار العينة القصدية من01 /10/2024 إلى 31/12/2024 المقدر عددها ب 128 منشورا بالاعتماد على أداة تحليل المضمون من خلال تصميم استمارة تحليل المضمون وتقسيمها إلى فئتين فئة الشكل كيف قيل؟ فئة المضمون ماذا قيل؟ وفي الأخير تم التوصل إلى النتائج التالية: تستخدم الصفحة الرسمية التواصلية للمؤسسة الاستشفائية المتخصصة احمد بن عبيد ببرج بوعريريج اللغة العربية في نشر مضامينها بنسبة % 98,44 تستخدم الصفحة الرسمية للمؤسسة الاستشفائية المتخصصة أحمد بن عبيد ببرج بوعريريج الصور في نشر مضامينها بنسبة % 60,66 يتفاعل الجمهور مع مضامين الصفحة الرسمية التواصلية للمؤسسة الاستشفائية أحمد بن عبيد ببرج بوعريريج بنسبة عالية من الاعجاب تقدر بنسبة % 88,69 ركزت الصفحة الرسمية التواصلية للمؤسسة الاستشفائية المتخصصة أحمد بن عبيد ببرج بوعريريج في منشورات الاعلانات على المواضيع الخاصة ببرنامج المناوبة لمستخدمي المؤسسة بالدرجة الأولى بنسبة85.14% الصفحة الرسمية التواصلية للمؤسسة الاستشفائية المتخصصة أحمد بن عبيد ببرج بوعريريج تهدف في عرض منشوراتها إلى ترسيخ الصورة الذهنية لدى جمهورها بنسبة% 48,99 تستهدف الصفحة الرسمية التواصلية لمؤسسة الاستشفائية أحمد بن عبيد ببرج بوعريريج في عرض مضامينها بالدرجة الأولى جمهور المواطنون بنسبة % 47,05 اتجاه الجمهور إيجابي نحو المواضيع الخاصة ببرنامج مديرية الصحة بنسبة 90,90 % الفاعل الرئيسي في الصفحة الرسمية للمؤسسة محل الدراسة هو"المواطنين "الجمهور" بنسبة 96,73 % الكلمات المفتاحية: استخدام، مواقع التواصل الاجتماعي، الفيسبوك، الصورة الذهنية للمؤسسة، المؤسسة الاستشفائية المتخصصة Abstract This study aims to explore the use of social media, particularly Facebook, in improving the image of the Ahmed Ben Abid Specialised Hospital in Bouarriridj. The hospital's official page was chosen as a case study based on the following question: How is Facebook used to improve the image of the Ahmed BenAbid Specialised Hospital in Bordj Bouarreridj among its audience? This study seeks to identify the following objectives: To understand the nature of the content published on the official Facebook page of the Ahmed Ben Abid Specialised Hospital in Bordj Bouarreridj To understand the nature of the language used in the content published on the official Facebook page of the institution under study. To identify the types of posts used by the institution under study on its official Facebook page. To monitor the level of audience interaction with the content published by the institution under study on its official Facebook page (in terms of the number of comments, likes, and shares.) To identify the objectives of the official page of the institution under study. To identify the target audience of the official page of the institution under study. Knowing the audience's trend towards the official page of the institution under study Identify the actors on the official page of the institution under study. To achieve the objectives of the study, a descriptive analytical approach was adopted by defining the variables of the study in the theoretical aspect. In the practical aspect, the posts on the official page of the institution under study were analysed by selecting a purposive sample from 01/10/2024 to 31/12/ 2024, estimated at 128 posts, using a content analysis tool by designing a content analysis form and dividing it into two categories: form (how was it said?) and content (what was said ?) Finally, the following results were obtained: The official communication page of the Ahmed Ben Obeid Specialised Hospital in Bordj Bou Arreridj uses only Arabic to publish its content on Facebook, at a rate of 98,44 %. The official page of the Ahmed Ben Abid Specialised Hospital in Bordj Bou Arreridj uses images to publish its content 60, 66 % of the time. The public interacts with the content of the official communication page of the Ahmed Ben Abid Specialised Hospital in Bordj Bou Arreridj with a high rate of likes, estimated at 88, 69%. The official communication page of the Ahmed Ben Abid Specialized Hospital in Bordj Bou Arreridj focused its announcement posts primarily on topics related to the on-call duty schedule for the hospital staff, accounting for 85.14% of all publications. The official communication page of the specialized healthcare institution Ahmed Ben Abid in Bordj Bou Arreridj aims to strengthen its image among its audience at a rate of 48,99 % , The official communication page of the Ahmed Ben Abid healthcare institution in Bordj Bou Arreridj primarily targets citizens at a rate of 47,05% , The public’s attitude is positive toward topics related to the Health Directorate’s program, with a rate of 90.90%. The principal actor on the official page of the institution under study is the audience, accounting for 96.73%.. The keywords: use, social networks, Facebook, image of the institution, the specialized hospital establishment.